Continuous-Variable Entanglement Generation from a Four-State Atom under Raman Excitation - 查婷婷 陈爱喜 杨文星 (Communications in theoretical physics, 2011)
We investigate the generation and the evolution of continuous-variable （CV） entanglement from a laser- driven four-state atom inside a doubly resonant cavity under Raman excitation. Two transitions in the four-state atom independently interact with the two cavity modes, while two other transitions are driven by coupling laser fields. By including the atomic relaxation as well as cavity losses, we show that the CV entanglement with large mean number of photons can be generated in our scheme. We also show that the intensity of the coupling laser fields can influence effectively the entanglement period of the cavity field. Different from the conventional resonant excitation scheme where zero one-photon detuning are required, it is found that the intensity and period of entanglement between the two cavity modes as well as the total mean photon number of the cavity field can be adjusted by properly modulating the frequency detuning.